Crystal structure of di-glycylglycinium squarate dihydrate, C12H22N4O12, at 105 K - Gomes Etelvina de Matos; Baptista Rosa M.F.; Görbitz Carl Henrik (Zeitschrift für Kristallographie - New Crystal Structures)
C12H22N4O12, triclinic, P1‾ $P\overline{1}$ (no. 2), a = 6.7126(4) Å, b = 7.7536(5) Å, c = 8.5279(5) Å, α = 89.4803(14)°, β = 86.2595(14)°, γ = 79.4035(14)°, V = 435.35(5) Å3, Z = 2, R gt(F) = 0.0323, wR ref(F 2) = 0.0908, T = 105(2) K.